Indigenous peoples and REDD+ safeguards: rights as resistance or as disciplinary inclusion in the green economy?. Issue 2 (September 2016) - Dehm, Julia
Abstract : This article critically evaluates the discourses concerning the social impacts of Reducing Emission from Deforestation and Forest Degradation (REDD+) carbon offset schemes on people living in and around forest areas. In particular, the article critically evaluates two of the strategies proposed to mitigate potential social risks from REDD+ and to promote benefits to forest peoples and indigenous peoples: tenure reform and processes of free, prior and informed consent (FPIC). The article suggests that these strategies may not lead to the outcomes forest peoples and their advocates are seeking and provide only constrained tools for contesting REDD+ projects. This article suggests these strategies may instead operate to facilitate the greater disciplinary inclusion of forest peoples in the so-called 'green economy'.